An efficient protocol for mass multiplication of Centella asiatica (L.) Urban and determination of its phenolic content - Kumari, Shweta; Trivedi, Maheshwar Prasad (Current Botany, 2021)
The present study was focused on standardizing a protocol for callus induction as well as regeneration in Centella asiatica from leaf and stem as explants. Stem and leaf explants have been inoculated in B5 media supplemented with BAP (0.1-2.5 mg/l), kn (01-04 mg/l) and NAA (0.1-0.5 mg/l), 2, 4-D (0.2mg/l) for callus induction. The combination of BAP and NAA leads to the formation of green, brown, compact and friable calli while Kn and 2, 4-D induced brown calli. Highest shooting was obtained from BAP (1.5 mg/l) and NAA(0.5 mg/l).When the shoots were inoculated in half strength of B5 media fortified with 0.1 mg/l BAP and 0.5 mg/l NAA showed cent percent rooting with the highest number of roots per shoot (11.05 cm) and maximum root length (1.86 cm). Stem showed the best explants for callus induction as compared to leaf explants. A low concentration of plant growth regulators was unable to induced callus response in leaf and stem explants. Phenolic content analysis showed that calluses contain more amounts of phenol (0.81 mg/gmdw) as compared to both leaf (0.63 mg/gmdw) and stem (0.59 mg/gmdw) explants.